Leadership of School Principals and Their Role in Improving the Quality of Education in Indonesia - Khairan, Ihsan; Junaidi, Junaidi; Supriadi, Supriadi (Yayasan Adra Karima Hubbi, 2024)
The current leadership of the school principal cannot be said to be good. This can be seen from the performance which is not yet optimal. The leadership of the school principal plays an important role, but some school principals are unable to carry out their duties well. This will of course greatly influence school activities which have an impact on the quality of education. This research aims to analyze the leadership of school principals in improving the quality of education. This type of research uses rivew literature using 6 articles. The data analysis technique uses qualitative analysis. The results of the research show that the leadership of school principals who have changes can improve the quality of education. Change by looking for innovative programs, improving student management in school culture, and disciplining them. The principal's leadership is formed by his character which provides a sense of comfort to the entire school community. A good school principal is able to foster a school culture and discipline, become a work partner, create cooperation between all school members to form a friendly and purposeful school environment. In this way, the leadership of the school principal can improve the quality of education in the institution where he serves..